Principles of translational science in medicine: from bench to bedside - Wehling, Martin (Elsevier Science, 2015)
Principles of Translational Science in Medicine: From Bench to Bedside, Second Edition, provides an update on major achievements in the translation of research into medically relevant results and therapeutics. The book presents a thorough discussion of biomarkers, early human trials, and networking models, and includes institutional and industrial support systems. It also covers algorithms that have influenced all major areas of biomedical research in recent years, resulting in an increasing numbers of new chemical/biological entities (NCEs or NBEs) as shown in FDA statistics.The book is ideal for use as a guide for biomedical scientists to establish a systematic approach to translational medicine.Provides an in-depth description of novel tools for the assessment of translatability of trials to balance risk and improve projects at any given stage of product developmentNew chapters deal with translational issues in the fastest growing population (the elderly), case studies, translatability assessment tools, and advances in nanotherapies Details IPR issues of translation, especially for public-private-partnershipsContains contributions from world leaders in translational medicine, including the former NIH director and authorities from various European regulatory institutions
Description based upon print version of record
Keywords: Electronic books